Amorphophallus bubenensis (Araceae), a new species from Yunnan, China - Yin, Jian-Tao; Yong, Luo; Liu, Jian-Wu; Liu, Qiang; Huang, Zi-Yun; Hetterscheid, Wilbert (Phytotaxa, 2016)
Amorphophallus Bl. in Decaisne (1834: 366) is a genus of about 200 species (Li & Hetterscheid 2010) of which 16 occur in China. Of these, 7 species are endemic to China. The new species adds the 8th endemic species to this flora.